ZR/RB RATIO IN THE CHINESE LOESS SEQUENCES AND ITS IMPLICATION FOR CHANGES IN THE EAST ASIAN WINTER MONSOON STRENGTH - Chen J.; Chen Y.; Liu L.; Ji J.; Balsam W.; Sun Y.; Lu H. (My University, 2006)
The long-term dust accumulation sequences on the Chinese Loess Plateau (CLP) provide a valuable opportunity to study the evolution of East Asian winter monsoon strength. Grain size of bulk samples of loess deposits, though widely used, is a modified measure of the strength of winter monsoon wind due to modification by post-depositional weathering and pedogenesis. This study proposes a new and reliable geochemical climate proxy that records the variability of the East Asian winter monsoon on the CLP. Six loess-paleosol sections on the Plateau were selected for measuring concentrations of the trace elements Zr and Rb as well as grain size. Variations of the Zr/Rb ratio in all the sections encompassing the last 130 ka display a generally similar pattern to that of mean grain size of bulk samples (MGSB). Though a positive correlation exists between the Zr/Rb ratio and MGSB, the correlation coefficient decreases in southern and eastern sections where intense pedogenesis occurred in the relatively warm and humid climates. Long-term Zr/Rb variation in the Lingtai section exhibits amplitudes and frequencies similar to those in MGSB and the mean grain size of quartz particles (MGSQ, accepted as a more reliable proxy than MGSB) in the upper loess-paleosol sequence over the past 2.6 Ma. However, for the underlying Red Clay formation, in the interval from about 7-2.6 Ma B.P., the MGSB record is relatively stable, whereas both the Zr/Rb ratio and MGSQ show distinct variability and display amplitudes similar to those observed in the overlying loess-paleosol sequence. These results demonstrate that the Zr/Rb ratio reflects original eolian grain size and may serve as a reliable index of the strength of East Asian winter monsoon winds. ? 2005 Elsevier Inc. All rights reserved.
Keywords: DUST; LOESS; MONSOON; PALEOCLIMATE; PROXY CLIMATE RECORD